Experimental Study on the Influence of Apigenin K and Melatonin in Socket Preservation as Bone Stimulators: An Experimental Study in Beagle Dogs - José Luis Calvo-Guirado (Applied Sciences, 2020)
The aim is to evaluate whether apigenin K and melatonin M5250 were able to stimulate bone formation after tooth extraction at one, two, and three months follow-up. Six male beagle dogs were used. Apigenin K and melatonin M5250 immersed in hemostatic collagen sponges were placed in the third and fourth premolar and the first molar extracted sockets; the second premolar was used as control. At one, two, and three months, bone core biopsies were performed, and picrosirius–hematoxylin was used for the staining process. In the first month, a higher amount of calcified bone tissue was observed in the melatonin (77.87% ± 1.2%) and apigenin K (69.81% ± 1.8%) groups than the control group (57.27% ± 0.54%), with apparent discrepancies in values between the three groups (p < 0.04). In the second month, there was a considerable improvement in the results in the areas with melatonin (79.81% ± 0.11%) than in those of apigenin K (71.65% ± 0.52%) and control (64.77% ± 0.44%) (p < 0.04). In the third month, the number of mature bone was similar to all the groups. The creation of new bone was significant in the melatonin group (82.78% ± 0.87%), followed by the apigenin K group (78.76% ± 0.43%) and the control group (57.27% ± 0.11%). From this experimental study in dogs, it can be concluded that melatonin and apigenin K can accelerate the process of mineralization of the bone matrix, and thus the creation of laminae in the early stages of healing (1 month). Less reabsorption of the post-extraction sockets can be expected with the topical application of melatonin and apigenin K. It seems that the stimulatory effects of bone healing induced by the topical application of melatonin and apigenin K are defect-size-dependent, being more evident in small defects compared to larger defects.